Smart Supply Chain Management Design, Methods and Impacts - Mubarik, Muhammad Shujaat; Khan, Sharfuddin Ahmed (Springer Nature Singapore : Imprint: Springer, 2025)
XIV, 247 p. 41 illus., 36 illus. in color.